Markets, fair trade and the Kingdom of God: essays to celebrate Traidcraft's 21st birthday - Johnson, Peter (Regnum [u.a.], 2001)
Part I. Some bigger issues Fair trade as Christian mission Chris Sugden -- Renewing the market place Peter Johnson -- Poverty-reducing development strategies : accepted and neglected challenges Deryke Belshaw -- Part II. Traidcraft's experience and future Beginnings and intentions Richard Adams -- Traidcraft's Christian basis and its relationship with its overseas partners Philip Angier -- Traidcraft and its staff Yvonne Dare -- Traidcraft and its fair traders Campbell Grant -- Traidcraft's Christian basis and the secular market place Stuart Raistrick -- Traidcraft and the churches Margaret Masson -- Resurrection and hope : Traidcraft's future David Nussbaum -- Appendices